Quantitative In Vivo Detection of Chlamydia muridarum Associated Inflammation in a Mouse Model Using Optical Imaging. (18th November 2015) - Patel, Manishkumar; Lin, Shu-An; Boddicker, Melissa A.; DeMaula, Christopher; Connolly, Brett; Bednar, Bohumil; Heinrichs, Jon H.; Smith, Jeffrey G.
Abstract : Chlamydia trachomatis is a bacterial sexually transmitted disease with over 1.3 million cases reported to the CDC in 2010. While Chlamydia infection is easily treated with antibiotics, up to 70% of infections are asymptomatic and go untreated. The current mouse model relies on invasive upper genital tract gross pathology readouts at 60–80 days postinfection. High throughput optical imaging through the use of biomarkers has been successfully used to quickly evaluate several disease processes. Here we evaluate Neutrophil Elastase 680 (Elastase680) for its ability to measure Chlamydia muridarum associated inflammation in live mice using fluorescence molecular tomography (FMT) and In Vivo Imaging System (IVIS). Optical imaging was able to distinguish with statistical significance between vaccinated and nonvaccinated mice as well as mock-challenged and challenged mice 2 weeks after challenge which was 9 weeks sooner than typical gross pathological assessment. Immunohistochemistry confirmed the presence of neutrophils and correlated well with both in vivo and ex vivo imaging. In this report we demonstrate that Elastase680 can be used as a molecular imaging biomarker for inflammation associated with chlamydial infection in a mouse model and that these biomarkers can significantly decrease the time for pathology evaluation and thus increase the rate of therapeutics discovery.